Runs of Homozygosity Preliminary Investigation in Pig Breeds - Yuqiang Liu; Guangzhen Li; Wondossen Ayalew; Zhanming Zhong; Xiaohong Liu; Jiajie Sun; Jiaqi Li (Animals)
Runs of homozygosity (ROH) are contiguous homozygous genomic segments that provide valuable insights into population history, selection pressures, and inbreeding levels. However, the global distribution of ROH and their implications for pig domestication and breeding are not yet fully understood. In this study, we analyzed whole-genome resequencing data from 1203 pigs across 49 breeds to characterize ROH patterns worldwide. European commercial pigs exhibited longer and more numerous ROH segments than Asian indigenous breeds, indicative of stronger artificial selection and higher inbreeding. Crossbreeding led to a reduction in ROH burden, with greater reductions observed when parental genetic divergence was larger. Notably, Asian and European pigs displayed distinct ROH islands, reflecting divergent selection pressures. Functional analysis revealed that these ROH islands were associated with growth, immunity, and reproduction. These findings enhance our understanding of the genetic diversity and selection history of global pig populations, providing valuable insights for future breeding strategies.